Enhanced case detection and improved diagnosis of PKDL in a Kala-azar-endemic area of Bangladesh. - Dinesh Mondal; Kamrul Nahar Nasrin; M Mamun Huda; Mamun Kabir; Mohammad Shakhawat Hossain; Axel Kroeger; Tania Thomas; Rashidul Haque (Public Library of Science (PLoS), 2010)
To support the Bangladesh National Kala-azar Elimination Programme (NKEP), we investigated the feasibility of using trained village volunteers for detecting post-kala-azar dermal leishmaniasis (PKDL) cases, using polymerase chain reaction (PCR) for confirmation of diagnosis and treatment compliance by PKDL patients in Kanthal union of Trishal sub-district, Mymensingh, Bangladesh. In this cross-sectional study, Field Research Assistants (FRAs) conducted census in the study area, and the research team trained village volunteers on how to look for PKDL suspects. The trained village volunteers (TVVs) visited each household in the study area for PKDL suspects and referred the suspected PKDL cases to the study clinic. The suspected cases underwent physical examinations by a qualified doctor and rK39 strip testing by the FRAs and, if positive, slit skin examination (SSE), culture, and PCR of skin specimens and peripheral buffy coat were done. Those with evidence of Leishmania donovani (LD) were referred for treatment. All the cases were followed for one year. The total population of the study area was 29,226 from 6,566 households. The TVVs referred 52 PKDL suspects. Probable PKDL was diagnosed in 18 of the 52 PKDL suspect cases, and PKDL was confirmed in 9 of the 18 probable PKDL cases. The prevalence of probable PKDL was 6.2 per 10,000 people in the study area. Thirteen PKDL suspects self-reported from outside the study area, and probable and confirmed PKDL was diagnosed in 10 of the 13 suspects and in 5 of 10 probable PKDL cases respectively. All probable PKDL cases had hypopigmented macules. The median time for PKDL development was 36 months (IQR, 24-48). Evidence of the LD parasite was documented by SSE and PCR in 3.6% and 64.3% of the cases, respectively. PCR positivity was associated with gender and severity of disease. Those who were untreated had an increased risk (odds ratio = 3.33, 95%CI 1.29-8.59) of having persistent skin lesions compared to those who were treated. Patients' treatment-seeking behavior and treatment compliance were poor. Improved detection of PKDL cases by TVVs is feasible and useful. The NKEP should promote PCR for the diagnosis of PKDL and should find ways for improving treatment compliance by patients.